Genetic characterisation of spontaneous ankylosing arthropathy with unique inheritance from Fas-deficient strains of mice. Issue 10 (28th March 2006) - Mori, S; Zhang, M-C; Tanda, N; Date, F; Nose, M; Furukawa, H; Ono, M
Abstract : Background: The spontaneous onset of macroscopic arthropathy in the ankle of the particular F1 mice descended from two Fas -deficient strains of mice; a mutant substrain of MRL/Mp. Fas lpr (MRL/rpl) and C3H/He. Fas lpr (C3H/lpr) was recently observed. Aim: To histopathologically characterise and genetically interpret the unique inheritance mode of disease in this arthropathy model. Methods: MRL/rpl, C3H/lpr, (MRL/rpl × C3H/lpr; MC) F1, (C3H/lpr × MRL/rpl; CM) F1 and MCF2 mice were bred under specific pathogen-free conditions. Histopathological grade of arthropathy was determined at 6 months by examination under a light microscope. To search for a linkage locus to the arthropathy, the whole genome of selected 48 male MCF2 mice with 71 polymorphic microsatellite markers was scanned, followed by quantitative trait locus analysis. Results: The incidence of microscopically defined arthropathy in the male and female MCF1 groups was 100% and 19.4%, respectively. No incidence was observed in the parental strains, MRL/rpl and C3H/lpr, and in CMF1 mice. In the MCF1 mice, the arthropathy mainly affected the ankle joints and was histopathologically characterised by marked entheseal proliferation with chondrocytic differentiation and ossification in the ankle joints, the manifestations similar to ankylosing enthesitis reported previously. An MRL/rpl-derived autosomal dominant susceptibility locus was mapped in the distal of D7Mit68 (60 cM) to the ankylosis onset. Conclusion: The MCF1 mice stably develop spontaneous ankylosing disorders in the ankle, with a male predominance. The unique inheritance mode of ankylosis is possibly interpreted by the genetic interaction between the autosomal dominant locus and a Y-linked locus.